Nanotwinned silver nanowires: Structure and mechanical properties. (15th June 2015) - Kobler, Aaron; Beuth, Thorsten; Klöffel, Tobias; Prang, Robby; Moosmann, Markus; Scherer, Torsten; Walheim, Stefan; Hahn, Horst; Kübel, Christian; Meyer, Bernd; Schimmel, Thomas; Bitzek, Erik
Abstract: Ag nanowires have been manufactured with the ultrathin layer electrochemical deposition method. Transmission electron microscopy revealed a multiple twinned nanostructure that has not been reported in comparable structures using a non-template self-assembling preparation method. The 1 1 1 twin planes are oriented parallel to the 〈1 1 2〉 wire axis. The influence of the twin boundaries on the elastic and plastic properties of these wires has been investigated. Atomistic calculations revealed no influence of the twin boundaries on the Young's modulus of the wire for this geometry and along the 〈1 1 2〉 direction. However, the twin boundaries exhibited a strong orientation-dependent influence on the plastic deformation when indented orthogonal (〈1 1 1〉 direction) or parallel (〈1 1 0〉 direction) to the twin boundaries, reflecting the interaction between the glide systems active in fcc metals and the stress direction. Heating experiments showed a high heat resistance for the twin boundaries till sublimation in an in situ TEM heating experiment. Sublimation followed the twin boundaries, indicating the lower binding energy of hcp stacking in comparison to fcc stacking.